(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article focal point on a number of issues, such as composition, color and form harmony, which are the laws of visual art in the artistic education of younger generations, their importance in creating an artistic work, analysis of works of art in the development of spatial creative power of the rising generation